АРХАИКАЛЫҚ ЭПОСЛАРДАҒЫ АТ ОБРАЗЫ - Көшекова, А.А. (ILIM hám JÁMIYET, 2025)
This article deals with the features of derived archaic epics. They included elements of the embodiment of the image of a horse in heroic epics. Despite the large number of preserved archaic motifs, the image of a horse in them does not rise to the rank of an individual, independent character, as in ancient epics, and these epics say that fantastic, archaic-mythological motifs are revised and revised in terms of concepts of the late era.